2014
DOI: 10.7860/jcdr/2014/7710.4327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Occupational Tobacco Exposure on Foetal Growth, among Beedi Rollers in Coastal Karnataka

Abstract: Introduction: Though there is ample evidence on adverse effects of tobacco exposure caused by smoking during pregnancy on foetal outcomes, there is lack of studies done on the effects of exposure caused by transdermal absorption, as is seen among beedi rolling women. Therefore, this study was planned, to assess the effect of maternal exposure to tobacco, in the form of beedi-rolling, on the birth weight and other neonatal anthropometric measurements. Materials and Methods:A cross sectional study with controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Overall, we found 95 studies (96 reports) assessing occupational health hazards of bidi workers and their families 8–10 12 18–108. We found eight studies from the grey literature, while 87 studies were published.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, we found 95 studies (96 reports) assessing occupational health hazards of bidi workers and their families 8–10 12 18–108. We found eight studies from the grey literature, while 87 studies were published.…”
Section: Resultsmentioning
confidence: 99%
“…We found six studies assessing the impact of bidi rolling on pregnant bidi workers 35 46 68 85 89 93…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have pointed out that beedi workers are particularly prone to a few types of occupational diseases such as eye issues, musculoskeletal system related diseases, pallor, high blood pressure and overweight (Basu et al, 2018), toxic optic neuropathy (Kaup et al, 2017), tuberculosis, lung cancer, gynaecological disorders, children born with congenital disorders (Mukherjee et al, 2014), joint pains, nervous system and skin diseases, high levels of creatinine in urine samples (Singh et al, 2014), respiratory impairment (Banu, 2014), and fatigue (Sabale et al, 2012). Beedi rolling in the third trimester during pregnancy is associated with a small, but a significant decline in birth weight and crown-heel length (Mandelia & Subba, 2014). Another study among the beedi workers of Udupi district in south India has found that a majority of the sampled workers have pain in their back, shoulders, knee joints and also suffer from sneezing bouts during beedi rolling, early morning coughs, sinusitis, pain in the fingers, nail discoloration, vision problems, watering of the eyes, musculoskeletal issues, and have respiratory, eye and skin problems (Sudina & Francis, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the Beedi making is carried out by the contractual, home-based, daily base system. In this women and children are involved quite easily 3 .Beedi is made by two main raw materials, tendu leaves (Beedi wrapper) and tobacco flakes. A single woman on an average rolls 500-1000 Beedi's per day, using an average of 500 grams of www.jmscr.igmpublication.org Impact Factor 5.84 Index Copernicus Value: 71.58 ISSN (e)-2347-176x ISSN (p) 2455-0450 DOI: https://dx.doi.org/10.18535/jmscr/v6i1.105 tobacco flake 2 .…”
Section: Introductionmentioning
confidence: 99%